Public sector audit and the state's responsibility to "leave no‐one behind": The role of integrated democratic accountability. (17th November 2022) - Cordery, Carolyn; Arora, Bimal; Manochin, Melina
Abstract: Achieving the United Nations (UN) sustainable development goals (SDGs) at country and local levels—and ensuring "no one is left behind"—requires that nation states commit to solving complex social and societal challenges through collaborative, democratic means. Technocratic and bureaucratic procedures alone are insufficient. In addition to satisfying international actors, governments must discharge integrated democratic accountability through inclusive stakeholder engagement with and between diverse and locally embedded social actors and institutions. Democratic accountability requires recognizing and preserving social complexity and plurality mediated through public dialogues between actors and institutions. Concurrently, global initiatives like the SDGs offer opportunities for the UN's member states to show their sincerity to international principles and standards while engaging with local practices that promote democratic means of resolution and policy implementation. This research analyzes how public sector audit can potentially support and hold a government accountable for its international pledges to SDGs, including stakeholder engagement. In India, the public sector auditor has proactively undertaken a performance audit on that government's "preparedness to implement SDGs." This research demonstrates how the government is held accountable for its policies and actions on SDGs, through analyzing the interrelated actions of India's two key democratic institutions—the Supreme Audit Institution and Public Accounts Committee. We make recommendations for improving state accountability for SDGs through national level policies, mechanisms and processes of stakeholder engagement and dialogues. At an international level, we argue for the UN to develop more effective mechanisms to hold governments accountable for policies and progress on their SDG commitments. Such mechanisms could include regular progress and performance audits and monitoring both nationally and internationally. These could contribute to improved leadership and integrated policy‐making across layers and levels within a nation state. We also highlight the areas for further research.